حالة سريرية (اقفار مساريقي حاد ) - سليمان, جمال (Latakia University Journal -Medical Sciences Series, 2020)
راجع السيد (ج. ب) اسعاف مشفى تشرين بقصة الم بطني حاد تالي لانسداد امعاء ميكانيكي خلال ال48 ساعة الماضية مع اقياءات طعامية مريحة وتطبل بطن وترفع حروري بالفحص تبين وجود تطبل بالبطن مع تخريش بريتواني تم اجراء الفحوص الشعاعية والمخبرية اللازمة (ايكوغرافي - طبقي محوري- صورة بطن بسيطة-تحاليل دموية) تبين وجود اقفار مساريقي حاد وتقرر عمل جراحي اسعافي (فتح بطن جراحي) حيث وجدت عروة صائمية متنخرة تم بترها واجراء مفاغرة معوية وتفميم صائم تم تخريج المريض بحالة جيدة .... (J.B ) a man (61 years old) was admitted to ER at tishreen university hospital due to acute abdominal pain secondered to mechanical intestinal obstruction within the last 48 hours. He had many comforting food vomitting , his abdomen was tender , and fever (39*c). On examination , there was abdominal tender with signs of peretonial irritation Radiology and laboratory tastes was made later ( abdominal x-ray – echography – ct scan – upper endoscopy) and the diagnosis was made , acute mesenteric ischemia . The patient was sent to OR for a lapartomy , a jejunal loop was found ischemic , and an end –to – end jejunojejunal anastomosis was performed , and a jejunal feeding tube was introduced. The patient was then discharged in a good state .